The Application of Management Information Systems in Improving School-Based Management at SMK Perwari Kendal - Muhammad Fauzi; Ajeng Arti Amalina (Fakultas Ekonomika dan Bisnis Universitas Selamat Sri, 2022)
Muhammad Fauzi. The purpose of this study is to find out how the application of Management Information Systems (MIS) in increasing school-based management (SBM) at SMK Perwari Kendal. The method used in this research is descriptive qualitative method. While the subjects in this study consisted of school principals, heads of administration and school operators. Data collection techniques in this study were carried out by means of interviews, observation and documentation. The results showed that the implementation of management information systems (SIM) at SMK Perwari Kendal had been implemented but had not been optimally implemented and there were still some obstacles in applying a management information system (SIM).